Transcriptome profiling of Nudix hydrolase gene deletions in the thermoacidophilic archaeon Sulfolobus acidocaldarius - Breuer, Ruth; Gomes-Filho, José Vicente; Yuan, Jing; Randau, Lennart (Frontiers in Microbiology, 2023)
Nudix hydrolases comprise a large and ubiquitous protein superfamily that catalyzes the hydrolysis of a nucleoside diphosphate linked to another moiety X (Nudix). Sulfolobus acidocaldarius possesses four Nudix domain-containing proteins (SACI_RS00730/Saci_0153, SACI_RS02625/Saci_0550, SACI_RS00060/Saci_0013/Saci_NudT5 and SACI_RS00575/Saci_0121). Deletion strains were generated for the four individual Nudix genes and for both Nudix genes annotated to encode ADP-ribose pyrophosphatases (SACI_RS00730, SACI_RS00060) and did not reveal a distinct phenotype compared to the wild-type strain under standard growth conditions, nutrient stress or heat stress conditions. We employed RNA-seq to establish the transcriptome profiles of the Nudix deletion strains, revealing a large number of differentially regulated genes, most notably in the ΔSACI_RS00730/SACI_RS00060 double knock-out strain and the ΔSACI_RS00575 single deletion strain. The absence of Nudix hydrolases is suggested to impact transcription via differentially regulated transcriptional regulators. We observed downregulation of the lysine biosynthesis and the archaellum formation iModulons in stationary phase cells, as well as upregulation of two genes involved in the de novo NAD+ biosynthesis pathway. Furthermore, the deletion strains exhibited upregulation of two thermosome subunits (α, β) and the toxin-antitoxin system VapBC, which are implicated in the archaeal heat shock response. These results uncover a defined set of pathways that involve archaeal Nudix protein activities and assist in their functional characterization.